A Novel Inquiry into a Strategic Aspect of Irish Women’s Theatre across a Century - Kurdi, Mária (Hungarian Journal of English and American Studies, 2022)
Book review:Hill, Shonagh. Women and Embodied Mythmaking in Irish Theatre. Cambridge: Cambridge UP, 2019. 257 pages. ISBN 978-1-108-48533-3. Hb. ₤75.